Evaluasi Kepatuhan Pelaku Usaha Petis Ikan HSN terhadap Sistem Jaminan Produk Halal (SJPH) di Konang Galis Kabupaten Pamekasan - Yulinda Tristiana; Ahmad Makhtum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In Pamekasan, many small and medium businesses have received halal certificates, but still have difficulty implementing SJPH in a sustainable manner. Many business actors do not fully understand that halal certification is not just a symbol, but is a system that needs to be implemented continuously and monitored closely. They often focus on the administrative aspects of certification, and ignore the importance of practice in daily activities. This research aims to determine the efforts of HSN fish paste business actors UMK in Pamekasan Regency in ensuring compliance with SJPH and evaluating compliance with SJPH implementation. The research method used is a descriptive qualitative research method, where the process of searching for data is through observation, interviews and documentation techniques. This method was chosen so that the research data is in-depth and comprehensive regarding the evaluation of HSN fish paste business actors' compliance with the Halal Product Guarantee System (SJPH). This research involved 4 fish paste business actors. The findings of this research show that HSN fish paste business actors are trying hard to implement SJPH, even though there are obstacles that hinder its effectiveness. However, there are weaknesses in supervision, internal auditing, and employee training. There needs to be more structured action to achieve optimal SJPH compliance and strengthen consumer trust.